Employer’s Assistant – new value in employing persons with disabilities. - Ramik-Mażewska, Irena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Irena Ramik-Mażewska, Employer’s Assistant – new value in employing persons with disabilities. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 417–432. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.20 The purpose of this article is to present the initiative of the West Pomeranian Voivodeship in Poland, which is aimed at increasing the professional activity of persons with disabilities. The developed and tested model of the employer’s assistant is, in the special pedagogy, a new quality directed towards the labour market. The Employer’s Assistant does not deal, in essence, only with a person with a disability, but mainly with the environment of employers to hire persons that suffer from disabilities. In the article, I refer to the assistant of the disabled person as a result of the biopsychosocial model of disability, which creates a great opening to the discussion on various models of assistance. I would like to point out the specific consequences of the lack of employment among people with disabilities. I present the premises of the employer’s assistant model and the evaluation of its effectiveness, the main consequence of which is the ability to build social capital of persons with disabilities. By cooperating with many environments, the employer’s assistant develops specific social behavioural patterns and becomes a foundation of social activity of persons with disabilities.